Development of a theoretical approach for investigating the occurrence of boredom in animals : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Manawatū, New Zealand - Heslop, Morgan Victoria (Massey University, 2024)
Many domestic and captive wild animals across the globe are kept under highly constrained conditions, and there has been a growing concern that boredom might represent a major source of welfare compromise for these animals. To understand how significant an impact animal boredom represents, there is first a need to improve understanding of what boredom is and how it can be recognised. The aim of this thesis is to systematically examine the concept of boredom and how it can be recognised in animals kept under human management. This investigation begins by reviewing current knowledge of boredom in humans, culminating in the presentation of a framework that demonstrates the relationships between the environmental antecedents, cognitive and physiological correlates, social and cultural features and behavioural outcomes of self-reported boredom. In humans, boredom is a temporally fluid emotion that is thought to function as a goal-switching signal, occurring when there is a mismatch between the availability of cognitive resources and environmental demands on those resources. The specific cognitive and behavioural changes associated with boredom are expected to change over time, but the pattern of these changes is not yet well characterised in humans, making it challenging to determine when to look for expected responses in animals. The framework is then used to identify which aspects of boredom are measurable and manipulable to systematically investigate boredom in animals. While various correlates are theoretically measurable, the most promising measures of boredom are behavioural; three behavioural strategies are expected to occur in response to boredom, characterised as goal-switching, goal-perseverance, and non-goal-related behaviour. Manipulations to increase the likelihood of boredom-related behavioural outcomes involve altering either the availability of the subject’s cognitive resources or the environmental demand, to produce a mismatch. A novel model is introduced to describe the predicted relationships between the expected behavioural pattern and the availability of cognitive resources relative to environmental demand, as well as perceived meaning of the current activity or task and the animal’s judgement of control during boredom. The model predicts that when there is a resource-demand mismatch, or when an activity/task is low in meaning, boredom will prompt behaviours that aim to either change goals or regulate cognitive resources and demand to support persevering towards the current goal. In situations where the subject does not judge adequate control to successfully alleviate boredom through these strategies, the model predicts the occurrence of non-goal-related behaviours. The model is used to investigate how existing research on environmental conditions and ‘enrichment’ (mainly through increased complexity) contributes to our understanding of boredom in animals. One important knowledge gap is understanding how a lack of change over time (i.e. monotony) is perceived as an antecedent to boredom in animals. The way monotony, so defined, may occur in the lives of animals is further explored. Although monotony is recognised as an antecedent of boredom in humans, it may not lead to boredom in all animals. The evolutionary background of a species is predicted to influence whether monotony is aversive to members of that species, and different types of monotony may be aversive to, or preferred by, different animals. Consideration of the key features of monotony led to the development of an experimental paradigm for investigating the behavioural outcomes of task-related monotony in rats, with a view to observing whether the predicted strategies associated with boredom occur during monotony in a species that is expected to find such conditions aversive. The planned experiment could only be completed with a single animal, and the data recorded could not be fully analysed within the timeframe of this PhD. Nonetheless, the paradigm provides a potential method for investigating how monotony is perceived by animals and identifying any associated welfare impacts. To date, there is a small amount of focussed evidence that animals in restrictive environments exhibit attempts to switch goals when opportunities are made available. However, most studies only report collapsed data such as the overall duration of different behaviours, precluding the recognition of behavioural patterns that indicate the occurrence of boredom according to the model developed here. Understanding these behaviours requires continuous monitoring to observe wider behavioural patterns over time. The model presented supports the systematic investigation of boredom in animals by generating predictions about the expected behavioural outcomes in situations with different features, which can be further examined and tested in future research. The exploration of boredom presented here contributes to a growing area of animal welfare science. The recognition and alleviation of boredom are both important and it is hoped that this work will contribute to a strong foundation that will support and provide rigour to future studies.
Keywords: animal welfare; boredom; animal behaviour; environmental enrichment; emotion; Cognition in animals; Animals; Psychological testing; Rats as laboratory animals; Behavior; 310901 Animal behaviour; 300306 Animal welfare; 300999 Veterinary sciences not elsewhere classified